Doktrin Alkitab: Suatu Kajian Teologis - Sarmauli Sarmauli; Yulianus Celcius; Elma Purwanti; Gabriel Stefanovit (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to understand and analyze the doctrine of the Bible as the foundation of Christian faith. The Bible plays a central role in various aspects of spiritual and ethical life for Christians. In the context of systematic theology, the doctrine of the Bible provides deep insights into the structure, authorship, and inspiration of this sacred text. This article examines several key issues, including the understanding of the doctrine of the Bible, the division of the books, the Bible’s authors, and the benefits and relevance of the Bible in spiritual life. Through an analytical approach to the doctrine of the Bible, this study seeks to elaborate on the role of sacred scripture in sustaining Christian faith amidst widespread false teachings and modern challenges.